Application of a flipped classroom teaching model based on micro-videos in the standardized training of dermatological residents in China - Li, Yang; Tang, Xian-fa; Cheng, Hui (Frontiers in Medicine, 2023)
Objective: To explore the effects of a micro-video-based flipped classroom teaching model on the standardized training of dermatological residents in China. Methods: A total of 78 residents who had received standardized training at the Department of Dermatology of the First Affiliated Hospital of Anhui Medical University were selected and randomly divided into an experimental group (39 residents) and a control group (39 residents). The experimental group received micro-video-based flipped classroom teaching, whereas the control group received traditional lecture-based classroom teaching. Scores relating to theoretical knowledge of dermatology, clinical practice skills, and the results of a questionnaire survey were used to evaluate the teaching effects. Results: The average score of the experimental group in the theoretical knowledge test (88.56 ± 5.80) was significantly higher than that of the control group (81.90 ± 7.45). Similarly, the average score of the experimental group in the clinical practice skills test (85.44 ± 5.97) was also significantly higher than that of the control group (78.46 ± 5.94). The results of the questionnaire survey showed that the experimental group exhibited significant improvements in learning interest, mastery of teaching content, communication skills, expression skills, clinical practice skills, autonomous learning, clinical thinking, clinical application, and team cooperation. Conclusion: Flipped classroom teaching based on micro-videos helped to improve the teaching effects of theoretical knowledge, clinical practice skills, and residents’ comprehensive ability during dermatological residents’ standardized training.